2005
DOI: 10.1073/pnas.0409405102
|View full text |Cite
|
Sign up to set email alerts
|

A negative elongation factor for human RNA polymerase II inhibits the anti-arrest transcript-cleavage factor TFIIS

Abstract: Formation of productive transcription complexes after promoter escape by RNA polymerase II is a major event in eukaryotic gene regulation. Both negative and positive factors control this step. The principal negative elongation factor (NELF) contains four polypeptides and requires for activity the two-polypeptide 5,6-dichloro-1-␤-D-ribobenzimidazole-sensitivity inducing factor (DSIF). DSIF͞ NELF inhibits early transcript elongation until it is counteracted by the positive elongation factor P-TEFb. We report a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 49 publications
(72 reference statements)
4
38
0
Order By: Relevance
“…4C). These results are consistent with the finding that human DSIF and NELF require transcripts ≥18 nt long to inhibit transcription (31), and also a recent study showed human DSIF preferentially bound elongation complexes containing transcripts that were at least 25 nt long (32). The 5′ end of an 18-nt-long nascent transcript just begins to emerge from the surface of Pol II (28,33).…”
Section: Dsif and Nelf Bind Cooperatively To The Pol II Elongation Cosupporting
confidence: 80%
“…4C). These results are consistent with the finding that human DSIF and NELF require transcripts ≥18 nt long to inhibit transcription (31), and also a recent study showed human DSIF preferentially bound elongation complexes containing transcripts that were at least 25 nt long (32). The 5′ end of an 18-nt-long nascent transcript just begins to emerge from the surface of Pol II (28,33).…”
Section: Dsif and Nelf Bind Cooperatively To The Pol II Elongation Cosupporting
confidence: 80%
“…In vitro biochemical characterization clearly demonstrate that NELF, of which COBRA1 is an integral subunit, modulates transcription elongation by stalling RNAPII at the promoter-proximal region (Yamaguchi et al, 1999;Palangat et al, 2005). Previous in vivo studies in human and Drosophila systems corroborate the RNAPII-stalling function of NELF in gene regulation (Wu et al, , 2005aAiyar et al, 2004).…”
Section: Discussionsupporting
confidence: 49%
“…Thus the MED31/SOH1 subunit of the Mediator displays genetic interactions not only with Pol II (34), but also with TFIIB (34) and several transcription elongation factors that include SII (35), the last in turn displaying close relationships with hSpt4-hSpt5/DSIF (36)(37)(38)(39). Furthermore, consistent with its role in early elongation, TFIIB has also been connected to diverse elongation and processing factors (40).…”
Section: Discussionmentioning
confidence: 89%